2019
DOI: 10.1364/ao.58.001682
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electric and magnetic dipole transition of rare-earth-doped thin films tailored by high-index dielectric nanostructures

Abstract: We propose a simple experimental technique to separately map the emission from electric and magnetic dipole transitions close to single dielectric nanostructures, using a few nanometer thin film of rare-earth ion doped clusters. Rare-earth ions provide electric and magnetic dipole transitions of similar magnitude. By recording the photoluminescence from the deposited layer excited by a focused laser beam, we are able to simultaneously map the electric and magnetic emission enhancement on individual nanostructu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…A similar comparison can be performed between the genetically optimized antenna and other commonly used dielectric resonators for enhanced magnetic fields such as a single silicon disk or a dimer of Si disks (see Figure S5, Supporting Information). Importantly, the magnetic field intensity enhancements simulated here for a disk dimer and a hollow nanodisk are in good agreement with recently reported experimental values, validating the relevance of the comparison made here. These simulations indicate that the GA design offers a very significant enhancement of the magnetic field intensity above the antenna that is 10× and 8× larger than for a single disk or a dimer, respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A similar comparison can be performed between the genetically optimized antenna and other commonly used dielectric resonators for enhanced magnetic fields such as a single silicon disk or a dimer of Si disks (see Figure S5, Supporting Information). Importantly, the magnetic field intensity enhancements simulated here for a disk dimer and a hollow nanodisk are in good agreement with recently reported experimental values, validating the relevance of the comparison made here. These simulations indicate that the GA design offers a very significant enhancement of the magnetic field intensity above the antenna that is 10× and 8× larger than for a single disk or a dimer, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Along the same lines, some of these structures were theoretically shown to strongly increase the emission rates of magnetic dipoles . In fact, experimental evidence for the capacity of optical nanoantennas to manipulate the emission of such dipoles at visible or near‐infrared wavelengths has been brought about recently. In that context, based on Mie resonances, high index dielectric nanoparticles are of particular interest to efficiently enhance the magnetic optical field at visible wavelengths through strong displacement currents taking place inside these nanoantennas .…”
Section: Introductionmentioning
confidence: 90%
“…In accordance with theoretical expectations, a moderate magnetic emission enhancement of about 3, as estimated by the authors, was observed. In another work [245], a homogeneous 10-nmthick film of Eu 3+ -doped nanoclusters was deposited on single silicon nanorods and dimers. The samples were raster-scanned under a tightly focused laser beam, and the PL maps were recorded.…”
Section: Magnetic Emission Enhancementmentioning
confidence: 99%
“…A physical interpretation of the mechanism causing the imaging process, has been highlighting the role of the electric part of the photonic local density of states (e-LDOS) at the emitter position [16]. Recently, delicate experiments have addressed light emission from rare earth doped emitters, supporting both, strong electric and magnetic dipolar transitions [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%